Sons and lovers - Lawrence, D. H. 1885-1930 (Oxford world's classics, 2009)
Lawrence's first major novel was also the first in the English language to explore ordinary working-class life from the inside. No writer before or since has written so well about the intimacies enforced by a tightly knit mining community and by a family where feelings are never hidden for long. When the marriage between Walter Morel and his sensitive, high-minded wife begins to break down, the bitterness of their frustration seeps into their children's lives. Their second son, Paul, craves the warmth of family and community, but knows that he must sacrifice everything in the struggle for independence if he is not to repeat his parents' failure